WikiLeaks and the problem of anonymity: A network control perspective. - Zajácz, Rita (Media, Culture & Society, 2013)
This article defines and applies the concept of “network control” as a tool for understanding the challenges and opportunities available to states as they seek territorial control over the global communications infrastructure. Through an analysis of the conflict between WikiLeaks and the US government on the tactical and structural levels, it reveals a contemporary dynamic of the territory–technology nexus of network control. From the perspective of the security establishment, the free speech aspect in the WikiLeaks case is tangential; the publication of sensitive information is just one of the many undesirable consequences of anonymity. Solutions to the problem so defined include the overhaul of the Pentagon’s network or “the Internet minus the anonymity,” which, if realized, will shape the future of the Internet.